2014
DOI: 10.1002/acr.22468
|View full text |Cite
|
Sign up to set email alerts
|

Lower Extremity Peak Force and Gait Kinematics in Individuals With Inclusion Body Myositis

Abstract: Objective. To determine the relationship between peak isometric muscle force and temporal characteristics of gait in individuals with sporadic inclusion body myositis (s-IBM).Methods. An observational study of 42 individuals with s-IBM (12 women; mean ؎ SD age 61.8 ؎ 7.3 years and mean ؎ SD disease duration 8.9 ؎ 4.3 years) was conducted at a federal hospital. Peak isometric force measurements for lower extremity (LE) muscle groups were obtained using quantitative muscle testing. Temporal characteristics of ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Notably, our older community-dwelling veteran participants (mean age, 62.5 ± 9.2) exhibited hand grip strength that was significantly associated with fast gait speed ( p = 0.02), but not customary gait speed ( p = 0.18). Our previous study of older adults with intrinsic muscle disease demonstrated that individuals may exhibit decrements in strength approaching 50% of normative values, yet still maintain walking speeds that exceed 1.0 m/s [ 44 ]. The redundancy in muscle group contributions to gait, and the role of ground reaction forces during stance phase, may obfuscate early muscle impairments when temporal gait parameters remain stable [ 25 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, our older community-dwelling veteran participants (mean age, 62.5 ± 9.2) exhibited hand grip strength that was significantly associated with fast gait speed ( p = 0.02), but not customary gait speed ( p = 0.18). Our previous study of older adults with intrinsic muscle disease demonstrated that individuals may exhibit decrements in strength approaching 50% of normative values, yet still maintain walking speeds that exceed 1.0 m/s [ 44 ]. The redundancy in muscle group contributions to gait, and the role of ground reaction forces during stance phase, may obfuscate early muscle impairments when temporal gait parameters remain stable [ 25 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study of older adults with intrinsic muscle disease demonstrated that individuals may exhibit decrements in strength approaching 50% of normative values, yet still maintain walking speeds that exceed 1.0 m/s [ 44 ]. The redundancy in muscle group contributions to gait, and the role of ground reaction forces during stance phase, may obfuscate early muscle impairments when temporal gait parameters remain stable [ 25 , 44 ]. Consequently, more demanding functional tasks, such as the fast walking test [ 25 ], may show a stronger association with local and global measures of strength as shown in this report.…”
Section: Discussionmentioning
confidence: 99%
“…In sIBM patients, very few studies have addressed the relationship between mechanical muscle function and functional capacity. The use of gait assistive devices has been associated with lower knee extension muscle strength, yet other reports have shown that gait kinematics are related to maximal muscle strength of the hip flexors/extensors, knee flexors/extensors, and plantarflexors . Recent modeling data indicate that maximal muscle strength in hip flexors, plantarflexors, and knee extensors, together with body weight, are important determinants of gait function in sIBM patients, and knee extensor strength and age at disease onset altogether predict the ability to step up onto a curb .…”
mentioning
confidence: 99%
“…Recent studies have looked at the frequency and circumstances of falls (Hiscock et al, 2014), and have analysed the abnormal gait patterns in patients with IBM (Bernhardt et al, 2011, Davenport et al, 2015 finding that there is a good correlation between knee extensor strength and functional lower limb measures such as the 2-minute and 6-minute walk tests (Lowes et al, 2012, Alfano et al, 2014. A smaller group of patients present initially because of weakness of the long finger flexor muscles, which is usually more severe in the non-dominant hand, or bulbar weakness, with lower limb weakness occurring at a later stage.…”
Section: Patterns Of Muscle Involvementmentioning
confidence: 99%